PLS MODEL FOR THE PRICE APPROACH OF CONCRETE SAND MATERIAL - Yulin Patrisia; Revianti Coenraad (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
This study aims to determine the factors that influence the pricing of sand concrete material in a project site and make an approach model to determine the price of relevant construction materials. The study was conducted through literature study and field survey to obtain primer data and secondary data. Approach model to fix the price of sand material by using PLS analysis. The result of research stated that there are several factors influencing the price of concrete sand material, namely economic factor, location factor, material resource factor, transportation factor, and regulation factor and government policy. The approach model to determine the price of concrete sand material shows that the transportation factor has an effect on the price of concrete sand material, while the least dominant variable is regulation factor and government policy.